Pemanfaatan Karbon Aktif dari Cangkang Kelapa Termodifikasi Fe₃O₄ sebagai Adsorben untuk Menurunkan Kadar Logam Seng (Zn2+) Limbah Cair - Yogi Chandra; Wahyu Triaji Rahadianto; Heni Sugesti (KATALIS: Jurnal Penelitian Kimia dan Pendidikan Kimia, 2026)
Environmental pollution originating from industrial waste, including waste containing heavy metals such as ions (Zn²⁺), is a serious concern due to its toxic nature, which can endanger human health. Efforts to treat heavy metal waste continue to be developed, one of which is through adsorption, which is considered efficient, inexpensive, and environmentally friendly. The use of composite-based materials, such as Fe3O4 and coconut shell activated carbon, offers great potential because it combines the magnetic properties of Fe3O4 and the surface area of activated carbon, thereby facilitating the separation process and increasing adsorption capacity. This study aims to evaluate the effectiveness of activated carbon derived from coconut shells and modified with Fe₃O₄ as an adsorbent to reduce the zinc ion (Zn²⁺) content in liquid waste. Activated carbon was modified with Fe₃O₄ to increase its adsorption capacity and facilitate the separation of the adsorbent after the process. Fe3O4-modified activated carbon was characterized using Scanning Electron Microscopy (SEM) to observe the surface morphology and texture, as well as to verify the success of the modification. The SEM characterization results showed changes in the surface structure of activated carbon after Fe3O4 modification. Adsorption tests were conducted in batches to determine the optimal contact time parameter. Contact time variations were tested to determine the adsorption kinetics (Zn²⁺). The results showed that Fe3O4-modified activated carbon had good adsorption performance for (Zn²⁺) ions, achieving a significant reduction in concentration. The optimal contact time for adsorption (Zn²⁺) was found to be 75 minutes, at which the adsorption efficiency (%) reached 90.1%. The conclusion of this study is that Fe3O4-modified coconut shell activated carbon is a potential, efficient, and environmentally friendly adsorbent for treating liquid waste contaminated with heavy metals (Zn²⁺).